2016
DOI: 10.1155/2016/5639875
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure, Membrane Interactions, and Toxicity of the Islet Amyloid Polypeptide in Type 2 Diabetes Mellitus

Abstract: Human islet amyloid polypeptide (hIAPP) is the major component of the amyloid deposits found in the pancreatic islets of patients with type 2 diabetes mellitus (T2DM). Mature hIAPP, a 37-aa peptide, is natively unfolded in its monomeric state but forms islet amyloid in T2DM. In common with other misfolded and aggregated proteins, amyloid formation involves aggregation of monomers of hIAPP into oligomers, fibrils, and ultimately mature amyloid deposits. hIAPP is coproduced and stored with insulin by the pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 127 publications
0
42
0
Order By: Relevance
“…4,5 hIAPP is believed to play a key role in the control of gastric emptying, glucose homeostasis and suppression of glucagon release. 6 It has been found that the oligomeric and/or brillar amyloid species of hIAPP leads to the death of b-cells and pancreatic dysfunction, contributing to islet transplant failure and T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 hIAPP is believed to play a key role in the control of gastric emptying, glucose homeostasis and suppression of glucagon release. 6 It has been found that the oligomeric and/or brillar amyloid species of hIAPP leads to the death of b-cells and pancreatic dysfunction, contributing to islet transplant failure and T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant aggregation of proteins into amyloid deposits is a hallmark of many human pathologies, for example, Alzheimer's disease, Parkinson's disease, and type 2 diabetes . Amyloid deposits contain amyloid fibrils characterized by cross‐β structure consisting of stacked β‐sheets held together by interpeptide hydrogen bonding along the long fibrillar axis .…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that incubation of human IAPP with cells results in formation of IAPP oligomers that are cytotoxic (21), which is at least in part mediated by direct cell membrane disruption by the oligomers, because the effect was also observed with cell-free lipid bilayers (22). We used human erythrocytes as a model to study membrane disruption during incubation with IAPP monomers.…”
Section: Discussionmentioning
confidence: 99%
“…The raw data were summarized and normalized using the Robust Multi Average algorithm (21) in which raw intensities are background-corrected, log2-transformed, and quantile-normalized. Normalized data were found to be of excellent quality with sample to sample correlations Ͼ0.98 and normalized unscaled standard errors close to 1.…”
Section: Methodsmentioning
confidence: 99%